2016
DOI: 10.1016/j.bbamcr.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen inhibits lipopolysaccharide-triggered NLRP3 inflammasome activation in macrophages by targeting the mitochondrial reactive oxygen species

Abstract: The NLRP3 inflammasome, an intracellular multi-protein complex controlling the maturation of cytokine interleukin-1β, plays an important role in lipopolysaccharide (LPS)-induced inflammatory cascades. Recently, the production of mitochondrial reactive oxygen species (mtROS) in macrophages stimulated with LPS has been suggested to act as a trigger during the process of NLRP3 inflammasome activation that can be blocked by some mitochondria-targeted antioxidants. Known as a ROS scavenger, molecular hydrogen (H2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 25 publications
4
34
0
2
Order By: Relevance
“…23 And it has been reported that hydrogen can regulate ROS activation in macrophages. 24 Our research shows that molecular hydrogen significantly attenuated high glucose-induced mitochondrial membrane destruction in peritoneal MCs and reduced intracellular ROS production, consistent with the findings of studies on hydrogen effects on cerebral ischemia-reperfusion injury. 25 The production of ROS in peritoneal MCs and during epithelial-mesenchymal transition of peritoneal MCs have been important targets for prevention and treatment of peritoneal fibrosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…23 And it has been reported that hydrogen can regulate ROS activation in macrophages. 24 Our research shows that molecular hydrogen significantly attenuated high glucose-induced mitochondrial membrane destruction in peritoneal MCs and reduced intracellular ROS production, consistent with the findings of studies on hydrogen effects on cerebral ischemia-reperfusion injury. 25 The production of ROS in peritoneal MCs and during epithelial-mesenchymal transition of peritoneal MCs have been important targets for prevention and treatment of peritoneal fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…High glucose peritoneal dialysate induces ROS production in peritoneal MCs, which promotes macrophage polarization to aggravate peritoneal mesothelial injury . And it has been reported that hydrogen can regulate ROS activation in macrophages . Our research shows that molecular hydrogen significantly attenuated high glucose‐induced mitochondrial membrane destruction in peritoneal MCs and reduced intracellular ROS production, consistent with the findings of studies on hydrogen effects on cerebral ischemia‐reperfusion injury …”
Section: Discussionsupporting
confidence: 89%
“…Previous studies showed that stimulation by LPS plus ATP could trigger the activation of NLRP3 inflammasome in RAW264.7 cells [38, 39]. Here, we observed that exposure to hyperoxia could result in NLRP3 inflammasome activation in RAW264.7 cells, which was consistent with the previous studies.…”
Section: Discussionsupporting
confidence: 83%
“…Inflammasome independent pathways are activated following the induction of metabolic stress through fatty-acid induced ETC uncoupling (Freigang et al, 2013). This alludes to the existence of other mechanisms for inducing inflammation following altered mitochondrial function that do not necessarily involve pathogens or oxidative stress (Ren et al, 2016). In macrophages mitophagy protects against inflammation which can limit tissue repair by reducing damaged mitochondrial signaling from the Nlrp3- inflammasome (Zhong et al, 2016).…”
Section: Mitochondrial Dysfunction and Damp Signaling In Inflammationmentioning
confidence: 99%